PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS KONSUMEN PT. POS INDONESIA CABANG BREBES - Slamet Nasroni (Jurnal Strategik, 2018)
ABSTRACT This study took the title "The Effect of Service Quality and Trust on Consumer Loyalty of PT Pos Indonesia Brebes Branch". The formulation of the problem in this study is (1) how the influence of service quality on customer loyalty PT. Pos Indonesia Brebes Branch; (2) how does the influence of trust on consumer loyalty of PT Pos Indonesia Brebes Branch; (3) how the influence of service quality and trust simultaneously on customer loyalty PT. Pos Indonesia Brebes Branch. The purpose of the study was to find out (1) the effect of service quality on consumer loyalty of PT Pos Indonesia Brebes Branch; (2) the influence of trust on consumer loyalty of PT Pos Indonesia Brebes Branch; (3) the influence of service quality and trust simultaneously on consumer loyalty PT. Pos Indonesia Brebes Branch .. The research hypothesis is assumed that (1) service quality has an effect on consumer loyalty of PT Pos Indonesia Brebes Branch; (2) trust has an effect on consumer loyalty of PT Pos Indonesia Brebes Branch; (3) service quality and trust simultaneously affect the loyalty of consumers of PT Pos Indonesia Brebes Branch. This research was conducted to examine the effect of service quality and trust in customer loyalty of PT Pos Indonesia Brebes Branch. The data analysis method used is quantitative analysis using the classic assumption test, t test, F test, coefficient of determination, and multiple linear regression analysis. The results of the study can be concluded that: 1. Testing the hypothesis by partially testing the service quality variable value of t arithmetic 2.1580 is greater than the value of t table 1.9758 and the significance value of the variable service quality 0.032 that value is smaller than 0.05 means the first hypothesis which states suspected service quality affect the customer loyalty of PT. Pos Indonesia Brebes Branch proved the results were significant. 2. Testing the hypothesis by partially testing the trust variable value t count 2.982 is greater than the value of t table 1.9758 with a significance value of 0.003, the value is smaller than 0.05, meaning that the second hypothesis states that it is believed that trust affects the customer loyalty of PT Pos Indonesia The Brebes branch proved the results were significant. 3. Testing the hypothesis by simultaneously testing the value of F count 12,185 greater than F table 3.0536 the significance value of 0,000 is smaller than 0.05 means that the third hypothesis is assumed that service quality and trust simultaneously affect the loyalty of consumers of PT Pos Indonesia Brebes Branch proved significant. Based on the results of the research and conclusions, it can be suggested: 63 1. For PT Pos Indonesia Cabang Brebes, the results of this study indicate that hypothesis testing partially or simultaneously on service quality variables and trust in loyalty is significant so it is recommended to the head of PT Pos Indonesia Brebes Branch to maintain and improve service quality and trust in consumers of PT Pos Indonesia Brebes Branch. 2. For further research, the author suggests to analyze the effect of service quality on loyalty, the effect of trust on loyalty using intervening trust variables.